Synthesis of Superabsorbent Polymer based Glucomanan-Polyacrylate by Gamma Irradiation - Sri Mulijani; Sri Sugiarti; Erizal Erizal; Qory Hajrul Fajriani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Materials with potential of fast absorption of water or liquid have emerged as very interesting objects for researches. Superabsorbent polymer is a cross linked polymer which has ability to absorb water hundreds to thousands of times the dry weight because it has hydrophilic groups. Owing to this characteristic this polymer gets attention for many applications, one of these is diapers. Superabsorbent polymer was synthesized from the mixture of glucomannan-pottasium acrylic-acrylamide solution by irradiation crosslinking with doses irradiation 10 kGy. It was found that SAP showed super swelling properties in water (880 g/g) at short time (15 minutes) and in real urine has a good swelling 110 g/g. Acrylamide was able to increase the swelling ratio in real urine. Therefore, it can be candidate as thin diapers with high sorption. The result of FTIR spectra confirmed that the crosslinkingoccurs in the hydrogels and SEM images of hydrogels showed large numbers of pores from SEM examinationKeywords: Superabsorbent polymer; Acrylic acid; Acrylamide; Glucomannan; Irradiation